Research on aging during the Venezuelan humanitarian crisis: the experience of the Maracaibo aging study - Gladys E. Maestre; Rosa V. Pirela; Carmen L. Paz; Jesus D. Melgarejo; Luis J. Mena; Carlos A. Chavez; Reinier Leendertz; Michele Petitto; Eglé Silva; Gustavo E. Calmón; Lama Al-Aswad; Joseph H. Lee; et al. (BMC, 2021)
Abstract Background Venezuela is in the throes of a complex humanitarian crisis that is one of the worst in decades to impact any country outside of wartime. This case analysis describes the challenges faced by the ongoing Maracaibo Aging Study (MAS) during the deteriorating conditions in Venezuela. When the MAS began in 1997, it focused on memory-related disorders. Since then, strategic planning and proactive community participation allowed us to anticipate and address logistical, funding, and ethical challenges, and facilitated the enrollment and retention of more than 2500 subjects over 55 years of age. All participants, who are residents of the city of Maracaibo, Venezuela, underwent various assessments on several occasions. Here, we discuss how our approach to implementing a longitudinal, population-based study of age-related conditions has allowed our research program to continue throughout this period of political, economic, and social upheaval. Discussion As the social context in Venezuela became more complicated, new challenges emerged, and strategies to sustain the study and participation were refined. We identified five main mechanisms through which the evolving humanitarian crisis has affected implementation of the MAS: 1) community dynamics; 2) morale of researchers, staff, and participants; 3) financial feasibility; 4) components of the research process; and 5) impact on the health of staff, participants, and their families. Strategies to compensate for the impact on these components were implemented, based on inputs from community members and staff. Improved communication, greater involvement of stakeholders, broadening the scope of the project, and strengthening international collaboration have been the most useful strategies. Particular demands emerged, related to the increased mortality and comorbidities of participants and staff, and deterioration of basic services and safety. Conclusion Although the MAS has faced numerous obstacles, it has been possible to continue a longitudinal research project throughout the humanitarian crisis, because our research team has engaged the community deeply and developed a sense of mutual commitment, and also because our project has provided funding to help keep researchers employed, somewhat attenuating the brain drain.